1988
DOI: 10.1093/ajcn/47.1.139
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and nutrient intake in middle-aged Scottish men

Abstract: The relation between alcohol consumption and dietary intake was examined in 164 middle-aged Scottish men taking part in a study of risk factors for coronary heart disease (CHD). A 7-d weighed dietary record was used to assess alcohol and nutrient intake. The mean daily intake of alcohol was 26 g (SD 31 g). Energy derived from alcohol tended to replace energy derived from other nutrients and increasing intake of alcohol was associated with a decrease in the amounts of carbohydrate, total fat, and saturated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 12 publications
4
31
0
Order By: Relevance
“…BMI increased regularly for both sexes from 13.5 and 13.2 for the 1-4-year age group to 22.2 and 23.5 for the age group above 50 years, and there was no sex differences ( Table 1). The corresponding BMI value(s) of Nepalese appear(s) to be similar to that of vegetarians in the Netherlands (20.9, 23-year-old males) [7] and to be lower than the values of Samoan men (24.4-26.2, 23-26 years) [8], of English men (25.4-26.4, 45-54 years) [9], and of American (15.3-26.1 and 15.0-24.4, 6-50 years old, for white males and females, respectively) [10]. The mean serum Chol level for males was 107 mg/ 100 ml for the 1-4-year age group, increased to 193 mg/ 100 ml for the 40-49-year age group, and decreased to 147 mg/ 100 ml at above 50 years of age (Table 2).…”
Section: Methodsmentioning
confidence: 76%
“…BMI increased regularly for both sexes from 13.5 and 13.2 for the 1-4-year age group to 22.2 and 23.5 for the age group above 50 years, and there was no sex differences ( Table 1). The corresponding BMI value(s) of Nepalese appear(s) to be similar to that of vegetarians in the Netherlands (20.9, 23-year-old males) [7] and to be lower than the values of Samoan men (24.4-26.2, 23-26 years) [8], of English men (25.4-26.4, 45-54 years) [9], and of American (15.3-26.1 and 15.0-24.4, 6-50 years old, for white males and females, respectively) [10]. The mean serum Chol level for males was 107 mg/ 100 ml for the 1-4-year age group, increased to 193 mg/ 100 ml for the 40-49-year age group, and decreased to 147 mg/ 100 ml at above 50 years of age (Table 2).…”
Section: Methodsmentioning
confidence: 76%
“…However, one study suggested a J-shaped relationship, with the highest level of alcohol intake associated with an increase in BMI 2 . In men, some studies have not found any relationship between alcohol consumption and BMI 2,10,22 , but others showed either a positive association 12,19,23,24 or an inverse one 19,20 . A J-shaped relationship was reported in non-smoking men; non-drinkers and subjects with a daily intake $ 36 g dl 21 had a higher body weight than moderate drinkers 25 .…”
Section: Discussionmentioning
confidence: 98%
“…One further clinical observation, stated originally in 1950,1 needs reemphasis: namely, that greater intensities of anticoagulant therapy are required immediately after the onset of an acute thrombotic process than are necessary to prevent recurrences. 2 Support for some of the views expressed here comes from clinical trials reported since the manuscript by Stults and co-workers was accepted for publication.24 Moreover, after considering the variables inherent in the prothrombin time assay itself, in the many features that may promote bleeding, in the knowledge that administration may involve a lifetime of use, and that many of the patients most needing long-term prophylaxis are in their 70s and 80s, it would appear reasonable to suggest that a majority ofthe group I patients at risk of systemic embolism can probably be managed at the low-dose ratios. In deciding on low-or medium-dose warfarin regimens, one must appreciate that the terms "low-risk" and "high-risk" patients depend both on the accumulated risk factors that a patient brings to the present illness and on the degree of thrombogenicity induced by the illness itself.…”
mentioning
confidence: 99%